Peran Guru Dalam Meningkatkan Keterampilan Membaca Pada Siswa Kelas II SD - Dewi, Kurnia Is Utami (Universitas Sebelas Maret, 2020)
The duties and responsibilities of a teacher include creating an atmosphere or climate for the learning process that can motivate students to always study well and enthusiastically. The teacher's role is as an educator, teacher, mentor, director, trainer, assessor, and evaluator of students. Reading is a language skill that has a very important role in life. Cultured and educated humans make reading a necessity in communication. By reading students will easily get knowledge and insight from anywhere. Based on the above, it can be concluded that without good reading skills, students will not be able to understand the learning process and the material being taught. Therefore, the teacher's role is needed in improving reading skills in second grade elementary school students.